Handbook of research on effective online language teaching in a disruptive environment - Swanson, Peter; LeLoup, Jean Willis (IGI Global, 2022)
"This book creates an innovative knowledge base about teaching during disruptive times in the context of K-20 language learning that is supported with empirical evidence and will serve as a reference for the advancement of research on, and the practice of, teaching and learning languages in both theoretical and practical ways